PSYCHOLOGICAL REHABILITATION OF PERSONS RELEASED FROM CAPTIVITY AS A FUNDAMENTAL COMPONENT OF THE STATE REINTEGRATION SYSTEM: REGULATORY GUARANTEES - Svitlak, Iryna; Liashch, Oksana; Hrebenova , Valentina (Personality and environmental issues, 2026)
The article provides a comprehensive study of the psychological rehabilitation of persons released from captivity as a fundamental component of the state reintegration system under conditions of the full-scale war and the post-war recovery of Ukraine. It is substantiated that captivity constitutes one of the most severe forms of extreme psychological traumatization, accompanied by prolonged psychological pressure, isolation, physical and psychological violence, and resulting in complex adverse consequences for an individual’s mental health. It has been established that the consequences of captivity manifest themselves in the form of post-traumatic stress disorder, anxiety and depressive conditions, emotional maladjustment, impaired social functioning, and identity crisis, thereby necessitating long-term psychological support and post-isolation assistance.The article analyzes the contemporary regulatory and legal framework governing the right of persons released from captivity to psychological assistance and psychological rehabilitation. Particular attention is paid to the provisions of the Law of Ukraine «On the Mental Health Care System», the Law of Ukraine «On Social and Legal Protection of Persons Recognized as Having Been Deprived of Personal Liberty as a Result of Armed Aggression against Ukraine, and Their Family Members», as well as subordinate legal acts of the Cabinet of Ministers of Ukraine, the Ministry of Defense of Ukraine, and the Ministry of Internal Affairs of Ukraine in the field of reintegration of released persons.Special attention is devoted to the analysis of post-isolation decompression as the primary form of psychological rehabilitation aimed at stabilizing the psycho-emotional state, restoring a sense of safety, and facilitating the gradual processing of traumatic experiences. The expediency of implementing person-centered, trauma-informed, and resource-oriented approaches within the system of psychological rehabilitation for persons released from captivity is substantiated. It is established that contemporary state policy in the field of mental health is gradually transforming from a predominantly medical and compensatory model toward a post-traumatic growth model focused on restoring the adaptive potential of the individual and ensuring their social reintegration.